2017
DOI: 10.1038/s41598-017-02243-9
|View full text |Cite
|
Sign up to set email alerts
|

Low-cesium rice: mutation in OsSOS2 reduces radiocesium in rice grains

Abstract: In Japan, radiocesium contamination in foods has become of great concern and it is a primary issue to reduce grain radiocesium concentration in rice (Oryza sativa L.). Here, we report a low-cesium rice mutant 1 (lcs1) with the radiocesium concentration in grain about half that in the wild-type cultivar. Genetic analyses revealed that a mutation in OsSOS2, which encodes a serine/threonine-protein kinase required for the salt overly sensitive (SOS) pathway in plants, is responsible for the decreased cesium (Cs) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 55 publications
0
22
0
Order By: Relevance
“…However, due to the available information on shoot to grain 137 Cs + transfer, with coefficients for rice in the range of 0.2–0.5 (Figure b, c) (Ohmori et al ., ,b; Kato et al ., ), including that for plants of cv. Nipponbare grown on soils displaying low contents in exchangeable K + as in our second soil (Ishikawa et al ., ), radiocesium in grains in our WT‐c plants would undoubtedly have been high (>100 times higher than the permitted level). Under such conditions, and taking into account the huge difference in shoot 137 Cs + between WT‐c and oshak1 mutant plants (Figure g), it is very likely that the grains of KO plants grown on this soil would have had far lower 137 Cs + contents than the grains of WT‐c plants (by at least a factor of 10).…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…However, due to the available information on shoot to grain 137 Cs + transfer, with coefficients for rice in the range of 0.2–0.5 (Figure b, c) (Ohmori et al ., ,b; Kato et al ., ), including that for plants of cv. Nipponbare grown on soils displaying low contents in exchangeable K + as in our second soil (Ishikawa et al ., ), radiocesium in grains in our WT‐c plants would undoubtedly have been high (>100 times higher than the permitted level). Under such conditions, and taking into account the huge difference in shoot 137 Cs + between WT‐c and oshak1 mutant plants (Figure g), it is very likely that the grains of KO plants grown on this soil would have had far lower 137 Cs + contents than the grains of WT‐c plants (by at least a factor of 10).…”
Section: Resultsmentioning
confidence: 83%
“…Two different soils were used (Figure a). The first soil contained 7 × 10 3 Bq of 137 Cs + per kg of soil dry weight (DW), and a level of exchangeable K + (177 mg/kg DW) close to the recommended range for reducing radiocesium concentration in rice plants to levels allowing grain consumption (Figure a) (Kato et al ., ; Ishikawa et al ., ). T2 plants grown for 113 days in this batch of soil displayed low 137 Cs + in grains (Figure b), within the permitted range (<100 Bq/kg) permitted by the 2012 Food Sanitation Act (Ohmori et al ., ).…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Even the ecotype screening for cesium transporters pointed out AtCNGC1 ( CYCLIC-NUCLEOTIDE-GATED CHANNEL 1 ) as potential causal gene, which is the close homolog of AtCNGC2 , a known K + transporter (Kanter et al, 2010). In another study, OsSOS2 had been shown to transport Cs + (Ishikawa et al, 2017). However, OsSOS2 was found to be indirectly linked to K + as in OsSOS2 mutant, K + and Na + transporter genes ( OsHAK1 , OsHAK5 , OsAKT1 , OsHKT2;1 ) are downregulated at low K + /Na + (Ishikawa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…In another study, OsSOS2 had been shown to transport Cs + (Ishikawa et al, 2017). However, OsSOS2 was found to be indirectly linked to K + as in OsSOS2 mutant, K + and Na + transporter genes ( OsHAK1 , OsHAK5 , OsAKT1 , OsHKT2;1 ) are downregulated at low K + /Na + (Ishikawa et al, 2017). It is predicted that Cs + uptake is reduced due to the lower expression of these transporters in presence of the K + /Na + imbalance (Ishikawa et al, 2017).…”
Section: Discussionmentioning
confidence: 99%